Charge-reversal proteolysis polymers enable tissue-specific STING degradation in rheumatoid arthritis - Xu He; Lidong Gong; Juqi Zhang; Xiaocong Pang; Yuhui Li; Wei Wei; Yimin Cui; Zhiqiang Lin (Proceedings of the National Academy of Sciences, 2026)
Inhibiting stimulator of interferon genes (STING) is critical for treating rheumatoid arthritis (RA), yet achieving precise suppression with high tissue specificity across protein variants remains challenging. Here, we engineer a multilevel, intelligent STING degrader—charge-reversal proteolysis-targeting chimeras (CreTACs)—that efficiently delivers to RA sites and degrades STING variants in humans, mice, and rats. Unlike traditional degraders with systemic toxicity, this charge reversal platform leverages pH-programmed charge inversion: Electroneutrality in circulation (pH 7.4) minimizes toxicity, while acidic-triggered protonation enables a 7.5-fold increase in arthritic joint accumulation (tissue level), pH-gated cellular internalization (80% uptake at pH 6.5 vs. 50% at pH 7.4; cellular level), and enhanced cytoplasmic STING (proton channel) affinity via charge interactions (protein level). In collagen-induced arthritis models, CreTACs outperformed methotrexate by suppressing synovitis and bone erosion without hematological toxicity. This multilevel charge reversal strategy establishes a blueprint for next-generation proteolysis drug-delivery systems or biomaterials, offering transformative potential for healthcare.